Microbial Contribution to Iodine Speciation in Hanford's Central Plateau Groundwater: Iodide Oxidation - Lee, Brady D.; Moser, Erin L.; Brooks, Shelby M.; Saunders, Danielle L.; Howard, M. Hope (Frontiers in Environmental Science, 2020)
A waste product from plutonium production at Hanford, the radioisotope iodine-129 (129I), is an environmental concern due to its long half-life, mobility, and hazardous potential to humans through bioaccumulation in the thyroid gland. Consequently, understanding the biological mechanisms and contributors to iodine speciation is important in order to increase our knowledge of iodine mobility and the overall risk to human health and the environment, and to evaluate remediation strategies for contaminated areas, as current remediation methods are insufficient and unsustainable. Although iodide (I-) is thermodynamically favored in the geological support material based on existing pH and Eh ranges at the Hanford Site, the dominant species of iodine found in groundwater and the vadose zone is iodate (IO3-). While microbial activity has been shown to catalyze the oxidation of I- to IO3-, this process has not been demonstrated by naturally occurring microbes found in the subsurface at the Hanford Site. Four microbial isolates enriched from Hanford groundwater were shown to oxidize I- to molecular iodine (I2) when grown on sugars and organic acids. Glucose proved to be the best substrate for growth, enzyme production, and I- oxidation. Multi-copper oxidases, such as laccase, have been shown to oxidize I-, and were produced during growth on glucose, xylose, and lactate. These results indicate that bacteria may play a significant role in groundwater iodine speciation (dominated by IO3-), as this form is not thermodynamically favorable and would not exist without transformation.